Identifying the Crash Worthiness and Crash Avoidance Factors Based on Road Features - Shokat Doaa M.; Jameel Abeer Khudhur (E3S Web of Conferences, 2023)
The increased rate of road fatalities ad injured has been a vital issue. Risk assessment of road projects is essential in the pre-construction stages to prevent road crashes from occurring in the operational stage. Identifying the contributing factors of road safety is essential to propose countermeasures and control the issue of the increase in road fatalities. These factors are categorized according to the transportation system's main elements: road users, infrastructure, and vehicles. They are also categorized according to the likelihood of crashes reflecting the crashworthiness factors and the severity of crashes reflecting the crash-occurrence factors. This paper aims to identify the factors related to road features affecting the likelihood and severity of crashes in a selected road section in Iraq. The selected road section is a portion of the main transport corridor, expressway 1/R9, designed to connect major cities and is used by significant traffic volume, leading to increased crash fatalities. The selected section connects Al-Bushajal with Al-Malahima village in Ramadi City. The selected tool is the International Road Assessment Program (iRAP), a valid risk assessment at road networks. The assessment output is in terms of star rating and star rating score. A higher star rating means safer road conditions, while a higher star rating score means more dangerous road conditions. The assessment results show high vehicle risk levels, and two types of crashes are diagnosed as the most common. Road improvements that meet safety standards are proposed, such as resurfacing with adequate overlay, improving delineation, lighting, metal barriers for the median and passenger side, and using shoulder rumble strips. The assessment results after improvements show upgrading the star rating to the recommended minimum (4 and 5) for vehicle occupants.